2016
DOI: 10.1002/jbm.a.35788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macrophages on in vitro corrosion behavior of magnesium alloy

Abstract: The influence of cells on the corrosion behavior of biomedical magnesium alloy is an important but less studied topic, which is helpful for understanding the inconsistent corrosion rates between in vitro and in vivo experiments. In this work, macrophages were directly cultured on Mg-2.1Nd-0.2Zn-0.5Zr (wt %, abbreviated as JDBM) alloy surface for 72 or 168 hours. Macrophages retained good viability and the generation of reactive oxygen species (ROS) was greatly promoted on the alloy. Weight loss, Mg(2+) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…These results confirm the model of cell‐accelerated corrosion proposed by Gilbert et al suggesting that macrophages release reactive oxygen species under inflammatory conditions and thus promote corrosion . One of the potential reactive oxygen species occurring in vivo is H 2 O 2 .…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm the model of cell‐accelerated corrosion proposed by Gilbert et al suggesting that macrophages release reactive oxygen species under inflammatory conditions and thus promote corrosion . One of the potential reactive oxygen species occurring in vivo is H 2 O 2 .…”
Section: Discussionsupporting
confidence: 90%
“…Rolling (hot/cold), extrusion, equal-channel angular pressing (ECAP), high pressure torsion (HPT), drawing, forging are the most commonly-used process methods for BMs' properties enhancement. It has been reported that these severe plastic deformation methods have dramatically improved the mechanical strength [82][83][84][85], elongation [82,83,85], vickers' hardness [86][87][88], corrosion behavior [86,[89][90][91], biocompatibility [92] of BMs. Clearly these are adoptable and promising techniques for Zn-based BMs in the future.…”
Section: Hot/cold Workingmentioning
confidence: 99%
“…Zhang et al [97] studied the influence of macrophages on the biocorrosion of Mg-2.1Nd-0.2Zn-0.5Zr (abbreviated as JDBM). Macrophages were found to substantially increase the corrosion rate of this alloy, owning to the deposition of ROS onto the samples' surface.…”
Section: Macrophagesmentioning
confidence: 99%